Optimization of insulin pump therapy based on high order run-to-run control scheme. Issue 3 (July 2015) - Tuo, Jianyong; Sun, Huiling; Shen, Dong; Wang, Hui; Wang, Youqing
Highlights Two kinds of high order R2R control methods are presented to optimize the insulin pump therapy. Using the proposed method, both the basal and the bolus insulin are adjusted simultaneously. The proposed method can converge even when there are ±60 min random variations in meal timing or ±40% random variations in meal size.